Targeting NLRC5 in cardiomyocytes protects postinfarction cardiac injury by enhancing autophagy flux through the CAVIN1/CAV1 axis - Lingfeng Gu; Sibo Wang; Liuhua Zhou; Wenjing Wang; Yulin Bao; Ye He; Tongtong Yang; Jiateng Sun; Qiqi Jiang; Tiankai Shan; Chong Du; Zemu Wang; et al. (Communications Biology)
Abstract NOD-like receptor (NLR) family proteins are implicated in various cardiovascular diseases. However, the precise role of NLRC5, the largest member of this family, in myocardial infarction (MI) remains poorly understood. This study reveals that NLRC5 is upregulated in the hearts of both patients with MI and MI mice. Silencing NLRC5 in cardiomyocytes impairs cardiac repair and functional recovery, while its overexpression enhances these processes. Furthermore, NLRC5 promotes autophagy in cardiomyocytes, and its protective effects are diminished upon autophagy inhibition. Mechanistically, NLRC5 interacts with CAVIN1, facilitating its degradation and subsequent downregulation of CAV1, which in turn increases the expression of the ATG12-ATG5 complex to stimulate autophagy. Conversely, CAV1 overexpression partially suppresses autophagy and attenuates the improvements in cardiac function observed in NLRC5-overexpressing MI hearts. This study highlights the critical regulatory role of NLRC5 in modulating cardiomyocyte autophagy flux, suggesting that NLRC5 activation may represent a promising therapeutic strategy for MI.